Performance Investigation of a Solar Thermal Collector Based on Nanostructured Energy Materials - Zain, Muhammad; Amjad, Muhammad; Farooq, Muhammad; Anwar, Zahid; Shoukat, Rabia; Bandarra Filho, Enio P.; Du, Xiaoze (Frontiers in Materials, 2021)
The convective and conductive heat transfer between the solar collector and working fluids make the photothermal performance limited, a higher rate of heat loss occurs from the surface of the conventional absorber to the surroundings. Direct absorption solar collectors (DASC) are a favorable alternative for improved photothermal performance. In this study, simulation based on the performance of a nanostructured solar collector has been carried out using TRNSYS. The connective and conductive heat transfer from direct solar collectors were improved by using nanofluids, three different nanostructured materials, including CuO, GO and ZnO was used in this study. The analysis determines the outlet temperature of the working fluids passed through the direct solar collector. The TRNSYS model consists of a direct solar collector and weather model for Lahore city, the simulations were performed for the whole year for 1440 hours. The stability of these nanostructured materials in the water was investigated by using UV-spectrometer. Various performance parameters of direct solar collectors were determined, such as variation in outlet collector temperature, heat transfer rates. The numerical model has been validated with experimental results. The maximum outlet temperature of 63℃ was observed for GO based nanofluids. The simulation results show that for the whole year, nanofluids improved the performance of direct solar collectors. A significant improvement in the heat transfer rate of 23.52%, 21.11%, and 15.09% was observed for the nanofluids based on nanostructures of CuO, ZnO, and GO respectively, as compared to water. These nanostructured energy materials are beneficial in solar-driven applications like solar desalination, solar water, and space heating.